Pengaruh Promosi 9.9 Super Shopping Day terhadap Niat Partisipasi Pengguna Shopee - Pison Febrian; Hetty Karunia Tunjungsari (Jurnal Manajerial Dan Kewirausahaan, 2022)
Tujuan dari penelitian ini adalah untuk menguji pengaruh perceived temptation of price promotion, perceived fun of promotion activities, perceived categories richness of promotion dan perceived contagiousness of mass participation terhadap niat partisipasi serta menguji efek moderasi pada variabel perceived contagiousness of mass participation terhadap perceived temptation of price promotion, perceived fun of promotion activities dan perceived categories richness of promotion. Populasi dari penelitian ini adalah berjumlah 205 sample penelitian yang terdiri dari 89 responden yang berjenis kelamin laki-laki dan 116 berjenis kelamin perempuan yang turut berpartisipasi dalam promosi 9.9 Super Shopping Day. Metode penelitian yang digunakan dalam penelitian ini adalah convenience sampling dengan melakukan penyebaran kuesioner secara online yang kemudian data yang sudah didapatkan lalu diolah menggunakan SmartPLS 3.2.9. Hasil dari penelitian ini adalah perceived temptation of price promotion, perceived fun of promotion activities, dan perceived contagiousness of mass participation mempengaruhi niat partisipasi sedangkan perceived categories richness of promotion tidak dapat memengaruhi niat partisipasi. Lalu perceived contagiousness of mass participation dapat memoderasi perceived categories richness of promotion sedangkan perceived contagiousness of mass participation tidak dapat memoderasi perceived temptation of price promotion, perceived fun of promotion activities. The purpose of this study was to examine the effect of perceived temptation of price promotion, perceived fun of promotion activities, perceived categories richness of promotion and perceived contagiousness of mass participation on participation intentions and to examine the moderating effect of perceived contagiousness of mass participation on perceived temptation of price. promotion, perceived fun of promotion activities and perceived categories richness of promotion. The population of this study was 205 research samples consisting of 89 respondents who were male and 116 female who participated in the promotion of 9.9 Super Shopping Day. The research method used in this study is convenience sampling by distributing online questionnaires, then the data that has been obtained and then processed using SmartPLS 3.2.9. The results of this study are the perceived temptation of price promotion, perceived fun of promotion activities, and perceived contagiousness of mass participation affect participation intentions, while perceived categories richness of promotion cannot influence participation intentions. Then perceived contagiousness of mass participation can moderate the perceived categories of richness of promotion while perceived contagiousness of mass participation cannot moderate the perceived temptation of price promotion, perceived fun of promotion activities.